Long term inhalation of iloprost in a child with primary pulmonary hypertension: an alternative to continuous infusion. Issue 3 (1st September 2001) - Beghetti, M; Berner, M; Rimensberger, P C
Abstract : Primary pulmonary hypertension is a rare disease in childhood associated with a poor prognosis. However, during the past 10 years, pulmonary vasodilator treatment has somewhat improved its prognosis. Long term continuous infusion of prostacyclin (epoprostenol) has been shown to improve physical capacity and to reduce mortality in primary and secondary pulmonary hypertension. It has been reported in adults that daily repetitive inhalation of iloprost, a prostacyclin analogue, seems also suitable for long term therapy of pulmonary hypertension. Repetitive inhalation of iloprost was administered to a 5 year old boy with severe primary pulmonary hypertension. He showed continuous clinical improvement without any side effects over the three years of treatment. This treatment may offer an alternative to continuous intravenous prostacyclin infusion and obviates the need for a permanent central venous catheter.